Narrative Analysis: Uncovering the Truth of Stories - Lisa M. Baumgartner (Adult Education Research Conference, 2000)
The use of narratives as a data source has come under scrutiny (Phillips,1994, 1997). The purpose of this session will be to discuss "truth" as it relates to narratives and to demonstrate methods of narrative analysis using data from a study concerning identity formation in HIV-positive adults.